Experimental Study on the Seismic Performance of Insulated Single-Sided Composite Shear Walls under Different Shear Spans and Axial Compression Ratios - Qiang Sun; Shoufeng Zhang; Ke Liu; Xinyi Wu; Guowei Zhang; Bei Cheng (Advances in Civil Engineering)
The new insulated single-sided composite shear wall (NISCSW) composition involves setting a precast wall panel on one side and an insulation panel on the other side, with a middle cavity for casting concrete. To investigate the seismic performance of NISCSW under different shear spans and axial compression ratios, eight specimens are made, including six composite and two cast-in-place walls. The shear span ratio is controlled at 1.2 and 1.9, and the axial compression ratio is controlled at 0.1, 0.3, and 0.4. The specimens are subjected to quasistatic tests to analyze failure modes, hysteresis characteristics, stiffness degradation, displacement ductility, and energy dissipation capacity and to compare the seismic performance of the composite and cast-in-place walls. Results show that for each composite specimen, under the same axial compression ratio, the large shear span ratio specimen has a lower ultimate bearing capacity and faster stiffness degradation but better ductility and postyield energy dissipation capacity. Under the same shear span ratio, the high axial compression ratio specimen had a higher ultimate bearing capacity, slightly worse ductility, and similar stiffness degradation and energy dissipation capacity compared to other specimens. Compared with the cast-in-place specimen with the same axial compression ratio, the composite specimen failure mode and hysteresis characteristics are similar, and the ductility and energy dissipation capacity are comparable to the cast-in-place shear wall specimen, indicating that NISCSW has similar seismic performance to the cast-in-place shear wall under conditions of a large shear span ratio and high axial compression ratio. Based on the test results, the program ABAQUS is used to simulate the specimens. Compared with the test results, the simulated specimen failure mode is consistent with the test results, and the hysteresis and skeleton curves are consistent with the test curve, indicating that the model is correct, reliable, and can be verified with test results.